'Can You Hear My Cry?' Representing War and Trauma in Picturebooks for Peace from China, South Korea, and Japan. Issue 1 (February 2022) - Tan, Fengxia; Nelson, Claudia
Abstract : This article discusses the Picturebooks for Peace series, a collaboration between China, South Korea, and Japan focusing primarily upon World War II. In examining this series, we ask what these works are testifying to, how they represent trauma, and how picturebooks from countries with distinct political and cultural outlooks have been conceived and received in the different milieus. Our major contention is that it is through the manipulation of time and space that the creators of these works seek to persuade readers of the validity of their message. We look first at the picturebooks from China and South Korea, which share an ideological position inasmuch as they use the trauma caused by the Japanese invasion and its aftermath (including the Korean War) to criticise war's inhumanity. The second part of the article deals with the four Japanese picturebooks, which reflect on the reasons for or essence of war. The article then discusses the narrative and aesthetic devices these books employ to represent war.